Adolescentes mães acolhidas modelando a arte e a vida: entrelaces entre a experiência artística com a cerâmica e as ressonâncias na criação de si. - Medeiros, Rosilda Maria Sá Gonçalves de (2017)
The general objective of this doctoral research was to study the creativity expressions that emerged – either by means of listening or playing – during the participation of adolescent mothers in a ceramics workshop under the intervention of the researcher. The literature presents the complexity of the simultaneous experience of being an adolescent and a premature mother in an institutional tender care context. The literature also reveals the importance of artistic activities in pedagogical projects developed by NGOs as a means of symbolization and contribution to the promotion of personal reconstruction, self-esteem and social integration of minors at risk. The research was based on distinct epistemological fields – Winnicott‟s conception of creativity (psychoanalysis, the maturational process) and Ostrower‟s (art, the artistic process). It was developed in a facility which offers tender care services to minors who are under ajudicial protective measure, which is supported by a catholic NGO in Paraíba, where twenty open group meetings happened for two and a half months in which seven young people took partand out of which the cases of three adolescent mothers aged between 15 and 19 were studied. The methodology involved the ceramics workshop as the research locus and the main procedure used for collecting data was “playing” with clay (ceramicar), founded on the clinical reference of “playing” with “squiggle game” proposed by Winnicott; it also considered “materiality” as pointed out by Ostrower – in this case, materiality of clay associated with the language of ceramics. The data collection tools used were audio recordings, photographic record and field diary. In each case studied, an analytical reasoning, as outlined by Mezan, was used, with special emphasis on three basic analysis units: the capacity and ways of playing (playful expressions), the way of using clay (plastic art expressions), the way of talking (verbal expressions) or silence – combining narrative diagrams (conversations) with listening, observation and theoretical interpretation. The results of the research provided answers to the following questions: Which contents do the adolescent mothers express considering the institutional tender care context they live in? Can that which each one of them does with clay express an artistic creation and end up helpingtheir own creation? Can an intervention by means of listening and playing with clay by any chance function as a “potential space” and contribute for the subjects to progress with their lives while they simultaneously live the contexts of adolescence and maternity? Among the results of the research, it was found that those young mothers had a shared experience of artistic creation with the language of ceramics, and could increase their aesthetical and cultural repertoire. At the same time, it was observed the contribution given to them so that they could find, in the listening offered by the researcher as well as in the act of playing, conditions for assuming their difficulties and potentialities during the development of the research as they expressed and symbolized their subjective manifestations. Therefore, art has constituted an important element of self-creation (both clinical and therapeutic effects of the intervention).